2010
DOI: 10.1510/icvts.2010.243196
|View full text |Cite
|
Sign up to set email alerts
|

Chest drain insertion is not a harmless procedure – are we doing it safely?

Abstract: The incorrect insertion of a chest drain can cause serious harm or even death. All elective drains should be inserted in the 'triangle of safety' in line with the British Thoracic Society guidelines. The aim of this study was to test the awareness of junior doctors involved in inserting chest drains with these guidelines. Fifty junior doctors were questioned. Participants were asked to grade their experience of chest drain insertion and mark on a diagram where they felt was the optimum site for inserting a dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 11 publications
0
34
0
1
Order By: Relevance
“…10 A further study by Elsayed et al showed that only 44% of junior doctors indicated that they would insert an ICD in the triangle of safety. 11 Furthermore, only 58% of junior doctors working in surgery had sufficient knowledge for safe insertion of ICDs.…”
Section: Discussionmentioning
confidence: 99%
“…10 A further study by Elsayed et al showed that only 44% of junior doctors indicated that they would insert an ICD in the triangle of safety. 11 Furthermore, only 58% of junior doctors working in surgery had sufficient knowledge for safe insertion of ICDs.…”
Section: Discussionmentioning
confidence: 99%
“…The invasive procedure is associated with more complications if the doctor is inexperienced or inadequately trained [6, 7]. To perform a successful procedure, the doctor requires knowledge of chest wall anatomy [8], aseptic techniques, pleural ultrasound [9-11], and basic surgical skills, as well as experience with the pigtail catheter system and an understanding of the therapeutic and diagnostic qualities of the procedure. TPCT can be performed in two different ways: using the Seldinger technique or the trocar method (in some studies referred to as the direct method).…”
Section: Introductionmentioning
confidence: 99%
“…It seems that chest drain insertion through the safe triangle after local anesthesia is simple. However, less than 50% junior doctors could mark the safe triangle correctly for chest drain insertion 2 . If the chest drain is in the correct position, there should be swinging of the water column during patient's respiration and the gush of air coming out during patient's coughing.…”
Section: Resultsmentioning
confidence: 99%